Implementation of a Web-Based Zakat Impact Assessment System (Case Study: Berau District National Amil Zakat Agency) - Sri Maryani; Arizona Firdonsyah (Procedia of Engineering and Life Science, 2021)
The National Zakat Agency (BAZNAS) of Berau Regency is a non-structural government institution that manages zakat nationally and was established by the Ministry of Religion in accordance with the Indonesian Presidential Decree No. 8/2001. BAZNAS has the duty and function of collecting and distributing zakat, infaq and alms at the national level. KDZ system is a web-based system managed by BAZNAS which is a component that is interconnected with each other with the function and ability to collect, process, store and convey information to assess the impact of zakat on mustahiqs who receive zakat distribution in the hope that it can reduce the level of poverty in the State of Indonesia. This research was conducted with the aim of analyzing the impact of zakat on mustahiq household income, mustahiq spirituality, and mustahiq household conditions. Data collection in this study used 1 method, namely interviews, with the results of the study showing that BAZNAS Berau District had implemented the KDZ system well.